Ballistic transport simulation of acceptor–donor C3N/C3B double-wall hetero-nanotube field effect transistors. Issue 35 (29th August 2019) - Zhao, Jianwei; Cheng, Na; He, Yuanyuan
Abstract : The one-dimensional (1D) acceptor–donor (A–D) hetero-nanotube (HNT) has attracted much attention as a potential candidate for a channel structure of next-generation field effect transistors (FETs). Abstract : The one-dimensional (1D) acceptor–donor (A–D) hetero-nanotube (HNT) has attracted much attention as a potential candidate for a channel structure of next-generation field effect transistors (FETs). Herein, we designed A–D C3 N/C3 B double-wall (dw) HNTs by coaxially wrapping C3 N and C3 B nanotubes together. By using density functional theory (DFT) combined with the nonequilibrium Green's function (NEGF) formalism, we studied the electronic properties and ballistic transport behavior of C3 N/C3 B dwHNTs in comparison with the ones in vertical stacking contact. The remarkable charge transfer between C3 N and C3 B nanotubes and band hybridization in C3 N/C3 B dwHNTs originate from the strong intertubular π–π stacking interaction. In the simulated all-around-gated FET devices, (12, 0) C3 N/(6, 0) C3 B dwHNT with 2 repeated wrapping units possesses the optimal performance, including rectifying ratio and subthreshold swing (SS), by enhancing the A–D asymmetry. Our work suggests that coaxial wrapping is a method superior to vertical stacking in constructing A–D HNTs for high-performance electronic and optoelectronic devices based on 1D materials.